Online-based Learning Management System in the Industrial Revolution 4.0 Era: Reality in Islamic Higher Education - Monalisa; Khotimah Mahmudah; Ika Aryastuti Hasanah; Aryawira Pratama; Mayang Sastra Sumardi; Rahmadani Putri; Wahyuni Fitria; Edi Rozal; Rijal Alhazzy (Journal of Education Technology, 2023)
The impact of the industrial revolution 4.0 developments with physical and internet cyber systems in the education sector is the development of computer-based teaching which then propagates to the development of online learning and the use of e-learning media. With a combined system, distance learning occurs in a learning management system with web-based assistance platforms and social media which is the result of the development of Industry 4.0 during the 21st century. The main objective of this research is to analyze and compare student perceptions in implementing eight platforms of implementing an online-based Learning Management System at the tertiary level. Then, this study links students' perceptions in implementing online-based learning management with reference to three aspects of assessment; teaching and learning aspects, lecturer competency aspects, and infrastructure aspects. A quantitative approach with a survey design has been chosen. Sampling technique was purposive sampling and involved 147 respondents. The results concluded that the Zoom, Google Classroom and Whatsapp platforms were the most frequently used distance learning media and were also liked by students. Currently, not many lecturers use Moodle because there is not enough time to learn how to use Moodle and prepare all the resources to design the desired learning, while there are many alternative platforms that are easier to learn and use in a short time. The survey on the three aspects of daring learning has been agreed in detail and the results provide positive conclusions regarding the implementation of online-based learning in the past 4 years.